Wendell Phillips papers - Phillips, Wendell, 1811-1884.
Chiefly correspondence, together with financial records, printed speech, and clippings, mainly relating to speaking engagements or publications and also to family matters, political concerns, and slavery. Correspondents include Francis Jackson Garrison, William Lloyd Garrison, and James Redpath of the Boston Lyceum Bureau. Other correspondents include Hannibal Hamlin, John H. Lowell, Samuel J. May, and Lydia Dodge Cabot Parker
Digitized facsimile available.
Reformer, lecturer, and lawyer.
Collection material in English.
Keywords: Garrison, Francis Jackson, -- 1848-1916 -- Correspondence; Garrison, William Lloyd, -- 1805-1879 -- Correspondence; Hamlin, Hannibal, -- 1809-1891 -- Correspondence; Lowell, John H. -- Correspondence; May, Samuel J. -- 1797-1871 -- Correspondence; Parker, Lydia Dodge Cabot -- Correspondence; Phillips family; Redpath, James, -- 1833-1891 -- Correspondence; Boston Lyceum Bureau; Lectures and lecturing; Publishers and publishing; Slavery; United States -- Politics and government -- 19th century; Lawyers; Lecturers; Reformers